Brain microdialysis to assess trace elements dynamics in traumatic brain injury: An exploratory study - Adriano Bernini; Sébastien Lenglet; Mette M. Berger; Samia Abed-Maillard; Roy Thomas Daniel; Mahmoud Messerer; Mauro Oddo; Jean-Daniel Chiche; Marc Augsburger; Nawfel Ben-Hamouda (PLoS ONE, 2025)
Background Trace elements (TEs) status alterations in the brain have been linked to neurodegenerative diseases. However, data on TEs in living humans and in the post-traumatic conditions are scarce. Some TEs (copper – Cu, selenium – Se, zinc – Zn) are involved in essential antioxidant defence. This study aims to measure the evolution of TEs concentrations in the brain and serum of severe traumatic brain injury (TBI) patients over time. Methods Twenty adult patients with severe TBI were monitored using cerebral microdialysis (CMD) and blood sampling within three days of intensive care unit admission. TEs levels were measured using inductively coupled plasma system coupled to mass spectrometry. Results TEs concentrations of chromium – Cr, Cu, cobalt – Co, manganese – Mn, molybdenum – Mo, Se, and Zn were quantified in brain interstitial fluid and serum. While serum and CMD levels did not differ significantly for Co, Mo and Mn, and modest differences was observed for Cr and Zn, significant differences were observed for Cu and Se with higher serum levels (8–10-fold higher) compared to CMD. No correlation was found between serum and brain TEs levels, except for Mo. Conclusion This study provides novel TEs concentration data in living TBI patients, the largest differences between brain and serum being observed for Cu and Se, serving as a basis for further research on TEs dynamics in acute brain injury.